Pengaruh Variasi Tekanan Oksigen pada Torch terhadap Sifat Mekanik Sambungan Las Oxy-Acetylene pada Plat Aluminium 5052 - Rayhan Ihsan Nugraha; Riyan Ariyansah; Pancatatva Hesti Gunawan (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2026)
This research aims to analyze the effect of oxygen pressure on the oxy-acetylene welding process concerning the mechanical properties of weld joints on 5052 aluminum plates. The variations of oxygen pressure used were 30 kg/cm², 40 kg/cm², and 50 kg/cm², with the acetylene pressure kept constant for each sample. Hardness testing was conducted to evaluate the hardness distribution in the base metal, Heat Affected Zone (HAZ), fusion line, and weld metal. The results indicate that oxygen pressure significantly affects the hardness values in the weld area. At an oxygen pressure of 30 kg/cm², the hardness reached 65.7 HV. Increasing the oxygen pressure to 40 kg/cm² resulted in the highest hardness value of 98.9 HV, indicating optimal conditions for forming a denser microstructure. However, at an oxygen pressure of 50 kg/cm², the hardness decreased back to 65.7 HV, suggesting that excessively high oxygen pressure can negatively impact the solidification process. From this study, it can be concluded that an oxygen pressure of 40 kg/cm² is the optimal parameter for achieving the highest hardness in the weld area. This research emphasizes the importance of controlling welding parameters to attain the desired mechanical properties in aluminum 5052 weld joints.